The Importance of English Language in Tourism Sector: A Study in Socotra Island - AL-Ragdhi, Ahmed; AL-Rakbi, Abdulhamid; AL-Ragdhi, Khaled; Bin-Hady, Wagdi (Naifaderu Cipta Sejahtera, 2024)
Purpose This study aims to highlight the significance of English language proficiency for sustainable tourism development on Socotra Island. It explores the impact of enhancing English language skills among professionals in the tourism sector and local residents. Methodology The study utilizes a quantitative research approach, with a close-ended survey shared with 27 professionals in the tourism industry on the island.